INTER-SPECIFIC STERILITY IN COPRlNUS-A FACTOR IN BIOCONTROL OF WEED FUNGI IN MUSHROOM BED - A. K. DAS, R. P. PURKAYASTHA AND (Indian Phytopathology, 2002)
The objective of this study was to control weed fungi, particularly Coprinus species, in the paddy straw bed of Volvariella volvacea, an edible mushroom, without disturbing its fruit-body production. Coprinus cinereus produced .fruit-bodies in both petri dishes and culture flasks i.vhen inoculated with C. umbrellatus but no fruit-body was formed when paired with C. patouillardii gp. The rate of production (1.15 kg fresh wt./becVm2) of V. volvacea was maximum when paddy straw bed was spawned with V. volvacea, C. cinereus and C. patouillardii gp but minimum (0.55-0.69 kg/bed) when spawned with either C. patouillardii gp. or C. cinereus. Inter-specific sterility between C. cinereus and C. patouillardii gp. could be attributed to higher production of V. volvacea in the present study.